Selecting lymph node–positive patients for adjuvant therapy after radical prostatectomy and extended pelvic lymphadenectomy: An outcome analysis of 100 node-positive patients managed without adjuvant therapy. (9th December 2022) - Tamhankar, Ashwin Sunil; Patil, Saurabh; Singh, Shanky; Carbin, Danny Darlington; Mokal, Smruti; Ahluwalia, Puneet; Gautam, Gagan
Abstract: Objective: The aim of the study is to evaluate the effect of deferred androgen deprivation therapy on biochemical recurrence (BCR) and other survival parameters in node-positive prostate cancer patients after robot-assisted radical prostatectomy with bilateral extended pelvic lymph node dissection (RARP + EPLND). Materials and methods: Of the 453 consecutive RARP procedures performed from 2011 to 2018, 100 patients with no prior use of androgen deprivation therapy were found to be lymph node (LN) positive and were observed, with initiation of salvage treatment at the time of BCR only. Patients were divided into 1 or 2 LNs (67)—and more than 2 LNs (33)—positive groups to assess survival outcomes. Results: At a median follow-up of 21 months (1–70 months), the LN group ( p < 0.000), preoperative prostate-specific antigen (PSA, p = 0.013), tumor volume (TV, p = 0.031), and LND ( p = 0.004) were significantly associated with BCR. In multivariate analysis, only the LN group ( p = 0.035) and PSA level ( p = 0.026) were statistically significant. The estimated BCR-free survival rates in the 1/2 LN group were 37.6% (27%–52.2%), 26.5% (16.8%–41.7%), and 19.9% (9.6%–41.0%) at 1, 3, and 5 years, respectively, with a hazard of developing BCR of 0.462 (0.225–0.948) compared with the more than 2 LN-positive group. Estimated 5-year overall survival, cancer-specific, metastasis-free, and local recurrence-free survival rates were 88.4% (73.1%–100%), 89.5% (74%–100%), 65.1% (46.0%–92.1%), and 94.8% (87.2%–100.0%), respectively, for which none of the factors were significant. Based on cutoff values for PSA, TV, and LND of 30 ng/mL, 30%, and 10%, respectively, the 1/2 LN group was substratified, wherein the median BCR-free survival for the low- and intermediate-risk groups was 40 and 12 months, respectively. Conclusions: Nearly one fourth and one fifth of 1/2 node-positive patients were BCR-free at 3 and 5 years after RARP + EPLND. Further substratification using PSA, TV, and LN density may help in providing individualized care regarding the initiation of adjuvant therapy.